BASICS APPROACH TO PROVIDING THE BEST SELECTION OF SAMPLES FOR TRANSPORT UNITS OF BORDER - Oleksandr Y. Podolian (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
This article contains the tools and the overall sequence of actions designed to address the problem of acquisition of parks departments Border Service and the mobile units of the State Border Guard most effective models of vehicles.